5. ガンセキ シリョウ ノ ネンダイ ソクテイナンキョク VICTORIA LAND ノ DRY VALLEY チョウサ ホウコク - 島, 誠; シマ, マコト; SHIMA, Makoto (国立極地研究所, 1967)
P(論文) Fission track ages have been measured for the basement complex rocks and the Ferrar Dolente which occur in Dry Valleys, Victoria Land, Antarctica The Dais Granite, the Vida Granite and the Ferrar Dolente are 520, 200 and 150 million years old, respectively Fission track ages are in good agreement with the results obtained by other dating methods (K-Ar method and Rb-Sr method) departmental bulletin paper